Tendencies in the Cases for Crimes Against Property and the Courts’ Preventive Function - Markov, Pressiyan (Research Papers, 2020)
The double reduction in the number of criminal cases for crimes against property cannot be explained either by a decline in their perpetration nor by their low rate of solving by the police. Statistical analysis proves to be inefficient for explaining this phenomenon, so it is necessary to use legal reasoning. The reason is the amendment of Art. 218b of the Criminal Code, whereby the value of the property that is object of these crimes, under which they are sanctioned as administrative offences, is increased annually. Hence a great number of crimes against property are not accounted for by crime statistics. That is the reason art. 218b of the Criminal Code has to be amended as it was before 2010. Prior to repealing the interpretive acts of the Supreme Court concerning the courts’ preventive function, it is necessary to verify if the number of crimes against property has actually declined.
Keywords: Trend; Crimes against property; Reduction; Statistics